MAXIMUM BITE FORCE FOR CHILDREN ON PRIMARY AND PERMANENT TEETH: WITHIN SUBJECT COMPARISON - Mohd G Sghaireen; Al-Omiri MK; Santosh Patil; Rayan Sewelim; Mohammed K Alrewely; Kaled Wsheh; Yossef Alsharary; Ahed J AlKhatib (European Scientific Journal, ESJ, 2014)
The aim of this study was to record maximum occlusal bite force (MBF) in north Saudi children on primary teeth and compare it to MBF of permanent teeth on the same patient and to determine the effect of gender, age and body mass index on MBF. The study included 215 patients (108 males and 107 females). MBF was measured using a hydraulic occlusal force gauge. The average MBF at the primary teeth was (249.39+ 112 N) and the average MBF at the permanent tooth was (340.60 + 123.79 N). Difference between both teeth was assessed using a t –test . The average MBF was higher at the 6 tooth (P < 0.05) and MBF was higher in M/F patient. Taken together, The data of the present study revealed that there are two forces exerted by mastectomy muscles. These forces are bite force on first molar and bite force on second deciduous molar. These two forces make a model that needs to be further investigated.